Multiple Respiratory Virus Detection in Acute Respiratory Infection Patients in Mie Prefecture, Japan, 2021–2023 - Tomita, Yuriko; Okura, Hiyori; Mochizuki, Rika; Negoro, Manami; Yano, Takuya; Kobayashi, Yusuke; Takayama, Ikuyo; Taniguchi, Kiyosu; Watanabe, Shinji; Hasegawa, Hideki (Viruses, 2025)
The Coronavirus disease 2019 (COVID-19) pandemic significantly impacted the circulation patterns of respiratory viruses worldwide. To better understand viral circulation patterns during the transition from pandemic to endemic phase, we conducted comprehensive respiratory virus surveillance in Mie Prefecture, Japan, during 2021–2023, coinciding with the Delta-to-Omicron transition of Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2). We collected respiratory specimens from acute respiratory infection patients in medical institutions, detecting 19 respiratory viruses using real-time PCR in 1573 valid samples out of 1605 specimens. Demographic and clinical data were available for some specimens. SARS-CoV-2 Omicron strains showed a peak positivity of 15–25% during the epidemic, while respiratory syncytial virus and human rhinovirus/enterovirus exhibited one to two annual epidemic peaks up to 57%, and human adenovirus maintained a positivity rate of 5–20% throughout the year. Age-dependent analysis revealed the significant detection of multiple viruses, particularly in children under 2 years, with up to six viruses detected simultaneously in those under 5 years. Our findings demonstrate varied respiratory virus prevalence patterns, with some viruses remaining active during the Omicron epidemic, suggesting its limited impact on other viruses. This comprehensive approach should enhance the understanding of respiratory virus epidemic dynamics and inform public health strategies.